Luminescência opticamente estimulada em pastilhas de quartzo utilizando iluminação azul e verde - Neilo Marcos Trindade; Isabela Alves Ferreira; Matheus Cavalcanti dos Santos Nunes; Elisabeth Mateus Yoshimura; Makaiko Chithambo (Brazilian Journal of Radiation Sciences, 2024)
In this study, pellets fabricated from powdered rose quartz are investigated for their potential as ionizing radiation detectors, taking advantage of the abundant availability of quartz in the Earth's crust. For this purpose, optically stimulated luminescence (OSL) technique, using blue and green light stimulation, was used. The pellets were irradiated with a 90Sr/90Y beta source to doses from 80 to 550 mGy (dose rate = 0.08Gy/s). Analysis of the OSL decay curves showed a good fit with 3 exponential components (fast, medium, and slow). A linear dose-response relationship was observed within this interval of dose for both light stimulations. The repeatability of the OSL signal was found to be 3% for blue light and 2% for green light. Additionally, the fading experiment indicated that, after 1 hour, 41% and 35% of the OSL signal remains for blue and green stimulation, respectively. The results obtained highlight the promising usefulness of rose quartz-based pellets as effective detectors of ionizing radiation.